Study On Application Of Safety and Health Management System Based On SMK3 PP NO. 50, 2012 at PT. BITE, Bandung, West Java - Nur Ani (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study aimed to review and evaluate and provide an overview of the results of the application of SMK3 in PT. BITE based on SMK3 PP No. standards. 50 of 2012. The research method used was qualitative with data collection techniques carried out by means of interviews and observations using instruments in the form of checklist SMK3 PP No. 50 of 2012 to obtain primary data and secondary data. Data validity uses triangulation test. The results of this study indicate the level of SMK3 fulfillment at PT. BITE, Bandung at the initial level assessment (64 criteria) by 86% (2018 observations) and at the advanced level assessment (166 criteria) by 80% (2020 observation results). This shows the existence of continuous improvement efforts at PT. BITE in an effort to improve the welfare of the workforce in the form of achieving SMK3 application which is considered good